Bishop John Leonard Wilson (Singapore 1941-1949): Koinonia in suffering - Mak, SA (Association for Theological Education in Southeast Asia, 2022)
Despite a century of ecumenical efforts among Protestant churches, real koinonia remains as elusive as ever. This article introduces John Leonard Wilson, one of the early contributors to the formation of Trinity College (known today as Trinity Theological College) in Singapore, to emphasize his ecumenical spirit that continues to be a key characteristic of the college. Leonard Wilson’s war time experiences in Singapore and its aftermath as well as those of TTC’s co-founders, show koinonia working at a much deeper level beyond the loose associations, large gatherings and joint declarations commonly seen in modern ecumenical movements. Wilson’s imprisonment and torture experiences during the war, his wider contributions before and after the war, and his devotion to church unity continue directly and indirectly to influence the Singapore church’s larger story. Wilson’s almost-fanatical commitment to and practice of koinonia in the midst of harsh circumstances has demonstrated that real koinonia is possible, but it comes with a heavy price.